The Two Metamorphoses in Horace’s Second Roman Ode - Ferenczi, Attila (Acta Classica Universitatis Scientiarum Debreceniensis, 2025)
It has always been a much-debated question how the two final stanzas of Horace’s Second Roman Ode fit to what came before in this poem. This paper will venture to place the apparent anomaly of these two verses within a new context emphasizing the strong and traditional connection between the constitution of the Roman State and the pax deorum. The second section of the poem (verses 5-6) portrays the workings of virtus as something incompatible with the usual ways and protocols of the late Republican political procedure in Rome. The all-changing power can be regarded as an inevitable consequence of the nature of the virtus, but at the same time, it can cause religious anxiety from somebody seeing and understanding this transformation. The last two verses about a religious panic do not contrast with the poem’s previous passages but represent a new voice in the political discourse.